A comparative assessment of cigarette smoke aerosols using an in vitro air–liquid interface cytotoxicity test. (15th October 2015) - Thorne, David; Dalrymple, Annette; Dillon, Deborah; Duke, Martin; Meredith, Clive
Abstract: This study describes the evaluation of a modified air-liquid interface BALB/c 3T3 cytotoxicity method for the assessment of smoke aerosols in vitro . The functionality and applicability of this modified protocol was assessed by comparing the cytotoxicity profiles from eight different cigarettes. Three reference cigarettes, 1R5F, 3R4F and CORESTA Monitor 7 were used to put the data into perspective and five bespoke experimental products were manufactured, ensuring a balanced and controlled study. Manufactured cigarettes were matched for key variables such as nicotine delivery, puff number, pressure drop, ventilation, carbon monoxide, nicotine free dry particulate matter and blend, but significantly modified for vapor phase delivery, via the addition of two different types and quantities of adsorptive carbon. Specifically manufacturing products ensures comparisons can be made in a consistent manner and allows the research to ask targeted questions, without confounding product variables. The results demonstrate vapor-phase associated cytotoxic effects and clear differences between the products tested and their cytotoxic profiles. This study has further characterized the in vitro vapor phase biological response relationship and confirmed that the biological response is directly proportional to the amount of available vapor phase toxicants in cigarette smoke, when using a Vitrocell® VC 10 exposure system. This study further supports and strengthens the use of aerosol based exposure options for the appropriate analysis of cigarette smoke induced responses in vitro and may be especially beneficial when comparing aerosols generated from alternative tobacco aerosol products.